Aksiologi Pendidikan Islam: Penanaman Karakter Islami di MITQ Al Firdaus Wonogiri - Khoirin, Taufiq; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
Islamic education plays an important role in shaping the character and personality of individuals, with the aim of not only creating individuals who excel academically but also possess noble morals. Islamic education emphasizes the axiological dimension, which discusses the values and benefits of the knowledge being taught. Madrasah Ibtidaiyah Tahfizhul Quran (MITQ) Al Firdaus Wonogiri is an Islamic educational institution committed to instilling Islamic character in its students. This study aims to analyze how the instillation of Islamic character is applied at MITQ Al Firdaus, using an axiological approach to understand its relevance and impact on students. The research employs a descriptive qualitative method with data collection techniques including interviews, observations, and document studies. The results indicate that the instillation of Islamic character at MITQ Al Firdaus is carried out through integration in classroom learning, worship activities, and teacher role models. The impact is seen in the improvement of students' morals, making them more disciplined, honest, and caring towards others. Despite challenges such as differences in students' backgrounds and time constraints, the instillation of Islamic character remains effective through a holistic and sustainable approach.